Analysis of the differences between the volleyball teams and volleyball players by positions at the Olympic qualification tournament - Bajric, O.; Srdic, V.; Pospisil, F.; Mikic, B.; Basinac, I.; Bajric, S. (XX Scientific Conference.FIS COMMUNICATIONS 2017" in physical education, sport and recreation (Nis, Serbia, october 19-21st, 2017), 2017)
The research was conducted in eight volleyball teams of the senior Olympic qualification tournament, divided into two groups of four teams. The main goal of the research was to determine whether there are statistically significant differences between groups, volleyball teams of the Olympic Qualifying Tournament and players in the playing positions (shooter, corrector, lift, middle blocker, libero) in basic morphological characteristics (body height, body weight) and situational parameters (smash, block). In order to determine the differences between groups and players in player positions (shooter, corrector, lift, middle blocker, libero) in the basic morphological characteristics (body height, body weight) and situational parameters (smash, block), a series of t- a variance analysis as well as a Tukey test to determine which variables there are statistically significant differences. The results of t-tests show that players of group 1 and group 2 do not statistically significantly differ in body height or in the result of sputum, but a statistically significant difference in body weight and in the result of the block is established. The results of the t-test analysis also indicate that there is no statistically significant difference between the volleyball teams of different play positions in morphological characteristics and situational parameters. However, the results of the variance analysis suggest that players of almost all different playing positions inter differ statistically significantly in morphological characteristics and partly statistically significantly differ in the results of the situational parameters (spam, block).